Development of an exercise based injury prevention programme for string players - Ajidahun, Adedayo Tunde (My University, 2017)
Background: The art of making music is an occupational risk factor for health-related problems. Musculoskeletal problems are the most common health problems experienced by musicians and the prevalence of musculoskeletal problems ranged from 37 – 77 %. The upper extremity, neck and back are the most commonly affected areas. In Africa, the prevalence of musculoskeletal problems is not well documented. Only a few studies have reported the presence of musculoskeletal problems with a relatively small sample size which is not often reflective of the population. Several injury prevention strategies such as exercise, ergonomic and health education have been implemented to reduce the musculoskeletal problems in the developed countries. In South Africa, there is no documented evidence of an intervention to reduce musculoskeletal problems of musicians generally. Injury prevention strategies to prevent playing-related problems have been suggested and implemented most especially, health promotion, ergonomics and exercise. However, despite the exercise-based intervention, the prevalence of musculoskeletal problems in this population is still relatively high. It has been suggested that an exercise-based intervention should be developed based on the physical demands of playing a string instrument. Therefore, an exercise-based musculoskeletal injury prevention programme could reduce the incidence of musculoskeletal problems in string instrumentalists.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the Doctor of Philosophy.
Keywords: Excercise Based Injury; Musculoskeletal Diseases